S96 Neutrophil metabolism is reprogrammed in patients with acute respiratory distress syndrome. (11th November 2022) - Cooper, GM; Sadiku, P; Griffith, DM; Walmsley, SR
Abstract : Introduction and Objectives: Acute Respiratory Distress Syndrome (ARDS) arises from diverse intra- and extra-pulmonary insults and contributes to a substantial proportion of the global intensive care burden. Dysregulated neutrophilic inflammation underpins the subsequent acute lung injury central to this disease process. Recent work in our laboratory has demonstrated that, despite their adaption to function in nutrient and oxygen deplete inflammatory microenvironments, neutrophils respond to hypoxaemia and tissue hypoxia through global rewiring of inflammatory processes. 1 We showed that this results in a novel neutrophilic inflammatory phenotype, characterised by promotion and prolongation within the active neutrophil compartment, and which drives the immunopathogenesis of ARDS. 1 We now hypothesise that within ARDS patients' circulating pools of inactive neutrophils, there is a metabolic phenotype that correlated the observed functional signature. To test this, we sought to perform targeted metabolomic and proteomic analyses of inactive blood neutrophils from healthy volunteers and ARDS patients. Methods: Twenty patients (n=15 moderate-severe ARDS patients and n=5 healthy controls) were recruited to a single-centre cross-sectional study undertaken between 04/2020- 01/2021. Neutrophils were isolated from participants' whole venous blood. High-performance liquid chromatography and mass spectroscopy (HPLC-MS) was performed, enabling chemometric metabolomic and proteomic analyses. Results: In ARDS neutrophils, relative to healthy control cell samples, metabolite abundances and protein expression levels were indicative of elevated glycolytic, gluconeogenic, fatty acid oxidative and synthetic activity. Additionally, our findings were consistent with upregulated glucogenic amino acid catabolism and the remodelling of the tricarboxylate cycle. Furthermore, despite their preserved energy status, we also observed an increased capacity for oxidative phosphorylation. These findings are summarised in figure 1 . Conclusions: We identified a signature of profound energetic reprogramming within the circulating neutrophil compartment in ARDS patients, relative to healthy control individuals, supporting our hypothesis that increased neutrophil biosynthetic capacity underlies the functional remodelling of neutrophil inflammation seen in systemic hypoxaemia and tissue hypoxia. Future research will seek to understand how this altered phenotype arises and contributes to the aberrant neutrophilic inflammation observed in ARDS. Reference: Mirchandani AS, et al. Hypoxia shapes the immune landscape in lung injury and promotes the persistence of inflammation. Nat Immunol 2022. https://doi.org/10.1038/s41590-022-01216-z